Предмет доказування у кримінальних провадженнях щодо економічних злочинів - Романюк, В. В.; Romaniuk, V. V.; Віталій Романюк (Наукові перспективи. - 2023. - № 2(32). - С. 413-422, 2023)
Підкреслено, що предмет доказування – це перелік обставин, наявність чи відсутність яких потрібно підтвердити за допомогою зібраних доказів, зміст яких в конкретному кримінальному провадженні завжди враховується при прийнятті окремих процесуальних рішень, плануванні досудового розслідування тощо. Встановлено, що зміст обставин, що входять до предмета доказування, уточнюється залежно від особливостей механізму вчинення злочинів у сфері економіки, кримінально-правової кваліфікації діяння та конкретних завдань кримінального провадження на кожній з його стадій. Виокремлено наступні групи обставин, які підлягають доказуванню у кримінальних провадженнях про злочини у сфері економіки: обставини про механізм учинення злочинів у сфері економіки, їх кримінально-правові та криміналістично значущі ознаки; обставини, що забезпечують відшкодування завданих збитків; обставини, які впливають на індивідуалізацію кримінального покарання; обставини, що є підставою прийняття та вмотивування процесуальних рішень під час здійснення кримінального провадження.

It has been emphasized that the prosecutor, the head of the pre-trial investigation body, the investigator (detective) are obliged to comprehensively, fully and impartially investigate the circumstances of the criminal proceedings on crimes in the economic sphere, to identify both those circumstances that expose and those that exonerate the suspect, the accused, as well as the circumstances mitigating or aggravating his punishment, provide them with a proper legal assessment and ensure the adoption of legal and impartial procedural decisions. The analysis of scientific approaches and provisions of criminal procedural legislation to the definition of the concept and structure of the subject of evidence in criminal proceedings has been carried out. It has been emphasized that the subject of proof is a list of circumstances, the presence or absence of which must be confirmed with the help of collected evidence, the content of which in a specific criminal proceeding is always taken into account when making individual procedural decisions, planning a pre-trial investigation, etc. It has been established that the content of the circumstances included in the subject of proof are specified depending on the features of the mechanism of committing crimes in the economic sphere, the criminal-legal qualification of the act and the specific tasks of criminal proceedings at each of its stages. The following groups of circumstances have been singled out, which are subject to proof in criminal proceedings about crimes in the economic sphere: circumstances about the mechanism of committing crimes in the economic sphere, their criminal-legal and forensically significant features; circumstances ensuring compensation for damages; circumstances affecting the individualization of criminal punishment; circumstances that are the basis for making and motivating procedural decisions during criminal proceedings.

Подчеркнуто, что предмет доказывания – это перечень обстоятельств, наличие или отсутствие которых следует подтвердить с помощью собранных доказательств, содержание которых в конкретном уголовном производстве всегда учитывается при принятии отдельных процессуальных решений, планировании досудебного расследования и т.п. Установлено, что содержание обстоятельств, входящих в предмет доказывания, уточняется в зависимости от особенностей механизма совершения преступлений в сфере экономики, уголовно-правовой квалификации деяния и конкретных задач уголовного производства каждой из его стадий. Выделены следующие группы обстоятельств, подлежащих доказыванию в уголовных производствах о преступлениях в сфере экономики: обстоятельства о механизме совершения преступлений в сфере экономики, их уголовно-правовые и криминалистически значимые признаки; обстоятельства, обеспечивающие возмещение причиненного ущерба; обстоятельства, влияющие на индивидуализацию уголовного наказания; обстоятельства, являющиеся основанием для принятия и мотивирования процессуальных решений при осуществлении уголовного производства.
Subject of evidence in criminal proceedings regarding economic crimes
Keywords: Кримінально-процесуальне право. Criminal and Procedure Law. Уголовное процессуальное право; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; кримінальне провадження; criminal proceedings; уголовное производство; економічні злочини; economic crimes; экономические преступления; доказування; proving; доказывание; предмет доказування; subject of proof; предмет доказывания; досудове розслідування; pre-trial investigation; досудебное расследование; обставини, які підлягають доказуванню; circumstances to be proven; обстоятельства, подлежащие доказыванию